ANALISIS PENGARUH KUALITAS PELAYANAN DAN INOVASI PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS LAYANAN JASA KIANO DECORATION) - Liando, Irwan; Ambar Lukitaningsih; Nonik Kusuma Ningrum (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of service quality and product innovation on customer satisfaction and its indirect effect on customer trust, which acts as a mediator for Kiano Decoration service customers. The method used in this study is quantitative. Primary data were obtained from a questionnaire with 60 respondents and non-probability sampling using the Slovin formula. To test data quality, the researcher used validity and reliability tests. Data analysis was conducted using classical assumption tests, multiple linear regression, hypothesis testing, and Sobel tests. Based on the results of the study, it was found that service quality has a positive and significant influence on customer satisfaction with the service, product innovation does not have a positive and significant influence on customer satisfaction, service quality has a positive and significant influence on consumer trust, product innovation has a positive and significant influence on consumer trust, and consumer trust does not have a positive and significant influence on customer satisfaction.